2017
DOI: 10.5194/hess-21-5891-2017
|View full text |Cite
|
Sign up to set email alerts
|

A sprinkling experiment to quantify celerity–velocity differences at the hillslope scale

Abstract: Abstract. Few studies have quantified the differences between celerity and velocity of hillslope water flow and explained the processes that control these differences. Here, we asses these differences by combining a 24-day hillslope sprinkling experiment with a spatially explicit hydrologic model analysis. We focused our work on Watershed 10 at the H. J. Andrews Experimental Forest in western Oregon. Celerities estimated from wetting front arrival times were generally much faster than average vertical velociti… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 62 publications
1
10
0
Order By: Relevance
“…Andrews Experimental Forest in western Oregon, USA. WS10 is a small 10.2-ha (0.1-km 2 ) catchment (Figure 2) that has been the subject of extensive research on hillslope hydrology (e.g., Brooks et al, 2006;Brooks et al, 2010;Gabrielli et al, 2012;Harr et al, 1972;Harr, 1977;McDonnell et al, 2010;McGuire et al, 2007;Sollins et al, 1981;van Verseveld et al, 2009;Van Verseveld et al, 2017). WS10 was chosen because it has less-developed riparian areas at the lower end of the stream reach and more prevalent riparian areas in the upper reach as a result of multiple debris flows that removed near-stream soils and riparian vegetation (Graham et al, 2013), as well as unique, existing infrastructure.…”
Section: Field Sitementioning
confidence: 99%
See 1 more Smart Citation
“…Andrews Experimental Forest in western Oregon, USA. WS10 is a small 10.2-ha (0.1-km 2 ) catchment (Figure 2) that has been the subject of extensive research on hillslope hydrology (e.g., Brooks et al, 2006;Brooks et al, 2010;Gabrielli et al, 2012;Harr et al, 1972;Harr, 1977;McDonnell et al, 2010;McGuire et al, 2007;Sollins et al, 1981;van Verseveld et al, 2009;Van Verseveld et al, 2017). WS10 was chosen because it has less-developed riparian areas at the lower end of the stream reach and more prevalent riparian areas in the upper reach as a result of multiple debris flows that removed near-stream soils and riparian vegetation (Graham et al, 2013), as well as unique, existing infrastructure.…”
Section: Field Sitementioning
confidence: 99%
“…Gabrielli et al (2012) reported two distinct layers in the bedrock competency on hillslope A: a highly fractured and weathered layer that was approximately 1‐m thick and a less‐weathered layer with discrete fractures and occasional deep fractures. Near the stream, the depth to unweathered bedrock ranges from 0.1 to 0.6 m and gradually increases to 3 to 8 m up hillslope (Van Verseveld et al, 2017). At the base of hillslope A, there is a 10‐m long flume to capture lateral subsurface flow discharging to the stream channel ( McGuire et al, 2007).…”
Section: Field Sitementioning
confidence: 99%
“…In contrast, the outer and lower pairs, which are farther from the tree trunk, could be sensitive to flow occurring downward (infiltration) and away from the tree stem (downslope) at these locations. A lateral component of unsaturated hillslope flow after rainfall has been previous observed in this watershed (Harr, 1977;van Verseveld et al, 2017). These interpretations will be addressed more in the discussion of the measured and modelled data (Section 6.3).…”
Section: Measured Sp Datamentioning
confidence: 64%
“…Second, the presence of a non-linearity due to the water table intersection with the land surface creates a responsive zone (the variable saturated areas) for flows, while the transport response is still predominantly controlled by the transit times of the particles traveling in the groundwater compartment. Third, it is the total amount of groundwater stored that effectively conditions the particle velocity by modifying the Darcy velocity with the ratio 𝐴𝐴 𝜙𝜙 𝑑𝑑 𝜙𝜙 𝑡𝑡𝑡𝑡𝑡𝑡 (van Verseveld et al, 2017). In this model, these three effects contribute to dissociate celerity from velocity (McDonnell, 2017;McDonnell & Beven, 2014).…”
Section: A 2d Stratified Advective Transportmentioning
confidence: 99%